Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
This Selected Issues paper for Denmark shows that a demographic shift will have several impacts on the economy. The decline in the relative size of the labor force will result in relatively fewer goods produced. This effect will be particularly strong, because a large portion of the current baby-boomers are in their peak earning years, and their retirement will have a dramatic effect on productivity and on overall production. Demark has imposed a restrictive policy requiring that immigrants prove they have a job that meets wage and working condition standards before getting a work permit.